2013
DOI: 10.1371/journal.pone.0053862
|View full text |Cite
|
Sign up to set email alerts
|

Serum GP73, a Marker for Evaluating Progression in Patients with Chronic HBV Infections

Abstract: This study was designed to investigate the role of serum GP73 for diagnosing significant fibrosis in patients with chronic hepatitis B virus (HBV) infections. Two populations were enrollment. All subjects were patients with chronic HBV infections. First population included 761 patients, who received liver stiffness measurement; the second population included 633 patients, who undertaken liver biopsy, in which 472 patients with nearly normal ALT. All patients received serum GP73 test. The effect of GP73 recombi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
33
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 29 publications
4
33
1
Order By: Relevance
“…This raises the potential for serum GP73 to be a noninvasive marker for hepatic necroinflammation and liver fibrosis. Subsequently, several researchers demonstrated that serum GP73 levels were significantly correlated with the staging of fibrosis and that these levels were proposed as markers for the diagnosis of both significant liver fibrosis and cirrhosis in patients with chronic HBV infections. However, they did not look into the relationship of pathological grading or staging with elevated serum GP73 levels.…”
Section: Discussionmentioning
confidence: 99%
“…This raises the potential for serum GP73 to be a noninvasive marker for hepatic necroinflammation and liver fibrosis. Subsequently, several researchers demonstrated that serum GP73 levels were significantly correlated with the staging of fibrosis and that these levels were proposed as markers for the diagnosis of both significant liver fibrosis and cirrhosis in patients with chronic HBV infections. However, they did not look into the relationship of pathological grading or staging with elevated serum GP73 levels.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with our findings, Qiao et al . had also noticed that the increased serum GP73 in CHB patients with cirrhosis [24], and GP73 positive cells in the liver were gradually increased with the severity of liver fibrosis [25]. Therefore, serum GP73 could be considered a potential marker for cirrhosis.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, an established hepatocellular carcinoma (HCC) biomarker, serum Golgi protein 73 (GP73), was reported to be correlated with disease severity in chronic hepatitis B (CHB) . The increased serum GP73 in HCC is argued to be attributed to the presence of cirrhosis rather than HCC .…”
Section: Introductionmentioning
confidence: 99%